Respuesta :
Answer:
There are no solutions.
Step-by-step explanation:
8 ( 3x - 6 ) = 6 ( 4x + 8 )
→ Expand the brackets
24x - 48 = 24x + 48
→ Subtract 24x from both sides
There is no x's left therefore there are no solutions.
Answer:
The equation has no solution.
Step-by-step explanation:
Let's actually try solving this equation: 8(3x – 6) = 6(4x + 8)
Begin by performing the indicated multiplication. We get:
24x - 48 = 24x + 48
Subtracting 24x from both sides, we get -48 = 48, which is never true.
The equation has no solution.